Global research trends and hotspots in metabolomics of osteosarcoma: a decade-spanning bibliometric and visualized analysis - Tu, Jun-Bo; Liu, Tao; Li, Jun-Feng; Long, Jian; Wang, Xiu; Liu, Wen-Cai; Gao, Xing-Hua (Frontiers in Immunology, 2024)
Object：Osteosarcoma is a malignant tumor originating from the bones, commonly found in children and adolescents, especially in rapidly growing bone areas such as the knees and upper arms.In this study, we aim to delineate the evolution and convergence of research themes in osteosarcoma metabolomics over the past decade, identify major contributors, and forecast emerging trends that could direct future research efforts.Method：The bibliometric method has been applied to systematically analyze the literature in the field of osteosarcoma metabolomics. The relevant literatures were collected from the Web of